Liver Dysfunction in Hyperthyroidism - Khongsaengbhak T; Atthakitmongkol T; Tanwandee T (Hepatic Medicine: Evidence and Research)
Thitichaya Khongsaengbhak,1 Thanapat Atthakitmongkol,2 Tawesak Tanwandee2 1Department of Medicine, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, Thailand; 2Division of Gastroenterology, Department of Medicine, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Tawesak Tanwandee, Division of Gastroenterology, Department of Medicine, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, 10700, Thailand, Tel +66 2 419 7281-2, Fax +66 2 411 5013, Email tawesak.tan@mahidol.ac.th; tawesak@gmail.comBackground: Thyrotoxicosis is often associated with abnormal liver tests. This study aimed to characterize the clinical features and laboratory findings in thyrotoxic patients with liver abnormalities and to identify predictive factors for differentiating thyroid storm within this population.Methods: This is a retrospective review of thyrotoxic patients with hepatic dysfunction between January 2015, and January 2021, at Siriraj Hospital, Thailand. Univariate and multivariate analyses were performed to identify the factors associated with thyroid storm.Results: Among 771 thyrotoxic patients, 43 revealed abnormal liver tests within six months of diagnosis (5.58%). The mean age was 53.16 ± 15.10 years, with a female predominance (60.5%), and the majority (97.7%) were diagnosed with Graves’ disease. The most common comorbidities were atrial fibrillation, heart failure, and dyslipidemia. Hepatic dysfunction presented as non-specific, with 46.5% showing a cholestatic pattern, 30.2% a mixed pattern, and 20.9% a hepatocellular pattern. The most possible etiologies of hepatic dysfunction were hyperthyroidism-related hepatitis (41.9%) with atrial fibrillation with congestive hepatopathy (38.9%), concomitant with chronic hepatitis C infection (14.0%), and methimazole-induced hepatic dysfunction (9.3%). The younger age, congestive heart failure, and total bilirubin levels ≥ 3.0 mg/dL were independent factors in distinguishing clinical thyroid storm among thyrotoxic patients without thyroid storm.Conclusion: Liver abnormalities can be observed in patients with thyrotoxicosis. The possible causes are multifactorial, including hyperthyroidism-related hepatitis, atrial fibrillation with congestive hepatopathy, and chronic hepatitis C infection. Younger age, congestive heart failure, and total bilirubin ≥ 3.0 mg/dL were predictive factors for thyroid storm diagnosis among thyrotoxic patients.Keywords: hepatic dysfunction, hyperthyroidism, liver abnormality, thyrotoxicosis, thyroid storm